Implementation of vertical axis wind turbine on renewable energy based self-sustaining public street lighting system - Dewi Indriati Hadi Putri; Muhamad Praja Dewanata; Arditya Baskara Mahbubi; Liptia Venica; Muhammad Rizalul Wahid (University of Merdeka Malang, 2025)
Kutamanah village, located in Sukasari Sub-district, Purwakarta District, faces limited electricity networks in strategic locations such as connecting roads between settlements, which impacts residents' safety and activities, especially at night. To overcome this problem, a program to utilize the potential of wind energy with a Vertical Axis Wind Turbine (VAWT) as a source of electrical energy for Public Street Lighting (PJU) was carried out. This activity was carried out through several stages, namely surveying the location of VAWT and PJU placement points, assembling VAWT and PJU, training and mentoring in implementation as appropriate technology that local residents can utilize. The system is designed to produce stable electrical power by utilizing the average wind speed that suits local conditions, which is 8.3 m/s. The implementation results show that this system is able to produce a peak voltage of 17.48 V and a current of 3.2 A so that the power generated reaches 54.4 W, the power is sufficient to support the operation of Public Street Lights with 50 W 12 V power specifications. This program contributes to improving community safety and mobility while supporting the use of sustainable renewable energy at the village level.